2013
DOI: 10.1186/1471-2164-14-389
|View full text |Cite
|
Sign up to set email alerts
|

Skin transcriptome profiles associated with coat color in sheep

Abstract: BackgroundPrevious molecular genetic studies of physiology and pigmentation of sheep skin have focused primarily on a limited number of genes and proteins. To identify additional genes that may play important roles in coat color regulation, Illumina sequencing technology was used to catalog global gene expression profiles in skin of sheep with white versus black coat color.ResultsThere were 90,006 and 74,533 unigenes assembled from the reads obtained from white and black sheep skin, respectively. Genes encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 43 publications
9
60
2
1
Order By: Relevance
“…García-Gámez et al (2011) proposed that no single keratin gene is responsible for the coat color trait. Fan et al (2013) revealed that high expression of keratin only affected the strength of wool. Other researchers, however, have not found a relationship between keratin genes and fur color formation, and therefore, we did not study these genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…García-Gámez et al (2011) proposed that no single keratin gene is responsible for the coat color trait. Fan et al (2013) revealed that high expression of keratin only affected the strength of wool. Other researchers, however, have not found a relationship between keratin genes and fur color formation, and therefore, we did not study these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have also described a significant correlation between TYRP1 expression and fur color formation (Schmidt-Küntzel et al, 2005;Duchesnes et al, 2009). Fan et al (2013) showed that TYRP1 is the most differentially expressed color formation gene between black and white Sunit sheep. This result is consistent with the experimental results reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al found that 49 known coat color genes are expressed in sheep skin, of which 13 genes were highly expressed in black sheep skin. These upregulated genes encode components of melanosomes and their precursors such as dopachrome tautomerase (DCT), MATP, tyrosinase (TYR), and tyrosinase related protein 1 (TYRP1) [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of Fan et al (2013), there were upregulated genes encoding transcription factors regulating mRNA expression (e.g. MITF) in white skin tissue, whereas in black skin tissue several novel genes were detected.…”
Section: High-throughput Genetic Techniquesnext-generation Sequencingmentioning
confidence: 99%
“…This might exclude this gene as having an effect on spotted phenotype formation. Fan et al (2013) analysed skin transcriptomes from white and black merino sheep. The authors obtained over 100 million raw reads from both skin colour types using the Illumina sequencing technology.…”
Section: High-throughput Genetic Techniquesnext-generation Sequencingmentioning
confidence: 99%